Proporsi Tape Singkong (Manihot esculenta) dan Ekstrak Pakcoy (Brassica rapa) yang Berbeda Terhadap Mutu Kimia dan Organoleptik Jus - Hanandhina, Rana; Hartati, Fadjar Kurnia; Sucahyo, Bambang Sigit (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Avocado juice is one of the most popular preparations in the community, but avocado fruit is seasonal so that when it is not in season it becomes difficult to obtain or even unavailable, so it is necessary to seek alternative juices with flavors similar to avocado juice. One alternative is juice made from a mixture of cassava tape and pakcoy leaves. This study aims to determine how the proportion of cassava tape and pakcoy affects the chemical and organoleptic quality of the resulting product, and to determine the most optimal proportion to produce the best juice product similar to avocado juice. This study used a quantitative experimental laboratory method with a research design using a Completely Randomized Design with four treatments and three repetitions. Chemical test parameters include reducing sugar reduction with luff-schrool test method, crude fiber with gravimetric test method, vitamin C with iodimetry test. The organoleptic test (taste, aroma, and color) using 25 panelists. Data analysis used Duncan test for lab test results and Kruskal Wallis for organoleptic test. The results showed that (1) the proportion of cassava and pakcoy tape had a significant effect on reducing sugar content, fiber content, and vitamin C content. (2) Reducing sugar content, fiber content, and vitamin C content in cassava and pakcoy tape juice were higher than avocado juice. (3) Organoleptic test showed the best value in treatment J3 in the aspects of taste and color, and treatment J0 in the aspect of aroma. (4) The effectiveness test showed that treatment J3 had the highest value which was the best treatment of this study.